Coping With Dependence: A Logistics Strategy Based on Interorganizational Learning for Managing Buyer–Supplier Relations. Issue 4 (23rd December 2016) - Kull, Thomas J.; Ellis, Scott C.
Abstract : The rise of outsourcing has heightened interest in the role of logistics managers in coping with dependence in buyer–supplier relations. Buying firm dependence on a supplier potentially reduces supplier performance to expectations because the buying firm cannot leverage power to capture value in the relationship. Drawing from interorganizational learning theory, we advance a logistics strategy that consists of supplier cost analysis and supplier integration as a means to create value and thereby mitigate the negative effects of dependence. By facilitating the acquisition and use of knowledge, supplier cost analysis and supplier integration enable buying firms to identify improvement opportunities while engaging in collaborative supplier relations. Using survey responses from 222 buying firms, we find that while buyer dependence decreases the buyer's perceived supplier performance, supplier integration suppresses these negative effects. Furthermore, we show that supplier cost analysis is a valuable knowledge acquisition tool that logistics managers can use to enable supplier integration as a relational form of governance. As such, we provide new insights into interorganizational learning theory and suggest to logistics managers the important role supplier cost analysis plays in managing buyer–supplier relationships.